Hubungan Sumber Air dan Personal Hygiene dengan Kejadian Penyakit Kulit di Puskesmas Perumnas II - Mulhima Fitriani; Fathmawati Fathmawati; Yulia Yulia (Poltekkes Kemenkes Padang, 2024)
Skin diseases are diseases that are often found in society, such as leprosy, dermatitis, scabies and tinea versicolor. Causal factors that influence the number of skin disorders include polluted water sources and poor personal hygiene. The aim of the research was to analyze the relationship between water sources, physical water quality and personal hygiene with the incidence of skin diseases in the Perumnas II Community Health Center area. The research method used case control with a sample of 74 people consisting of 37 cases and 37 controls. The sample calculation was obtained using openpi.com with a confidence level of 95%. Cases were obtained from patients with skin diseases who sought treatment at the Perumnas II Community Health Center, controls were neighbors who did not suffer from skin diseases. Data collection by interview. Data analysis used the chi square test. The results of the study showed that there was a correlation between water sources and the incidence of skin diseases with p-value= 0.008 and OR (CI 95%)= 4.265 (1.545 – 11.771), there was a correlation between the physical quality of water and the incidence of skin diseases p-value= 0.000 and OR (CI 95%)= 6.692 (2.381-18.812) there is a correlation between personal hygiene and skin disease p-value= 0.001 and OR (CI 95%)= 7.529 (2,401-23,613). Conclusion: there is a relationship between water sources, physical water quality and personal hygiene with the incidence of skin diseases at the Perumnas II Community Health Center. It is recommended that the public pay more attention to the water sources that will be used for sanitation and hygiene needs.